1974
DOI: 10.1073/pnas.71.1.96
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Early Changes in Phosphate and Uridine Transport and Cyclic AMP Levels Stimulated by Serum in Density-Inhibited 3T3 Cells

Abstract: A kinetic study of the early changes in uridine-and phosphate-transport rates and 3':5'-cyclic AMP levels induced by the addition of serum to quiescent 3T3 cells revealed that the increase in phosphate uptake and the decrease in the intracellular concentration of 3': 5'-cyclic AMP immediately follow the addition of serum. In contrast, the increase in uridine transport occurred after a lag of several minutes and was clearly preceded by the other changes. The activation of phosphate transport involved an increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

1975
1975
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Incorporation of [3H]uridine was in creased approximately twofold in the presence of serum, but the degree of inhibition by 60 ~tM DRB was unchanged (67%) and again complete and prompt reversal of the inhibition was obtained upon removal of DRB after a 60-rain period of treatment. Increased uptake of uridine upon addition of serum to confluent cultures of mouse 3T3 cells has been reported previously (4,5). The serum stimulation observed in the present study occurred in incomplete monolayers of L cells.…”
Section: Kineticssupporting
confidence: 86%
“…Incorporation of [3H]uridine was in creased approximately twofold in the presence of serum, but the degree of inhibition by 60 ~tM DRB was unchanged (67%) and again complete and prompt reversal of the inhibition was obtained upon removal of DRB after a 60-rain period of treatment. Increased uptake of uridine upon addition of serum to confluent cultures of mouse 3T3 cells has been reported previously (4,5). The serum stimulation observed in the present study occurred in incomplete monolayers of L cells.…”
Section: Kineticssupporting
confidence: 86%
“…Certain effects of elevated Pi on cell behavior have been demonstrated to be cell autonomous. It was noted almost four decades ago that contact inhibited 3T3 cells respond to serum stimulation with a rapid increase in Pi transport (Cunningham and Pardee, 1969; de Asua et al, 1974; Barsh et al, 1977). Pi transport is regulated by a family of sodium dependent phosphate transporters (Werner et al, 1998; Collins et al, 2004; Tenenhouse, 2005).…”
mentioning
confidence: 99%
“…An early event during such activation with serum or insulin is the stimulation of uridine uptake [2]. Recent work has shown that it is not uridine transport but rather the subsequent trapping of uridine within the cell that is so enhanced [ 3 , 4 ] .…”
mentioning
confidence: 99%